2015
DOI: 10.3389/fpsyg.2015.01635
|View full text |Cite
|
Sign up to set email alerts
|

Visual processing in reading disorders and attention-deficit/hyperactivity disorder and its contribution to basic reading ability

Abstract: Whether visual processing deficits are common in reading disorders (RD), and related to reading ability in general, has been debated for decades. The type of visual processing affected also is debated, although visual discrimination and short-term memory (STM) may be more commonly related to reading ability. Reading disorders are frequently comorbid with ADHD, and children with ADHD often have subclinical reading problems. Hence, children with ADHD were used as a comparison group in this study. ADHD and RD may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 57 publications
(93 reference statements)
1
16
0
3
Order By: Relevance
“…For example, females are more often affected by anxiety disorders (Mclean, Asnaani, & Litz, ) and depression (Abate, ) that are associated with deficits in face processing and emotion perception. On the other hand, males have a higher risk of developing autism spectrum disorders (Werling & Geschwind, ) that show impaired emotional perception and are more vulnerable to attention deficit hyperactivity disorders (ADHD; Ramtekkar, Reiersen, Todorov, & Todd, ) that are related to attention, working memory, executive functioning deficits (Kibby et al, ) and reduced perception of anger (Manassis, Tannock, Young, & Francis‐John, ). Thus, investigating sex‐related differences in behavioral and neural responses, as well as brain structure, in larger samples of healthy observers will have important implications for identifying such sex differences in these psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For example, females are more often affected by anxiety disorders (Mclean, Asnaani, & Litz, ) and depression (Abate, ) that are associated with deficits in face processing and emotion perception. On the other hand, males have a higher risk of developing autism spectrum disorders (Werling & Geschwind, ) that show impaired emotional perception and are more vulnerable to attention deficit hyperactivity disorders (ADHD; Ramtekkar, Reiersen, Todorov, & Todd, ) that are related to attention, working memory, executive functioning deficits (Kibby et al, ) and reduced perception of anger (Manassis, Tannock, Young, & Francis‐John, ). Thus, investigating sex‐related differences in behavioral and neural responses, as well as brain structure, in larger samples of healthy observers will have important implications for identifying such sex differences in these psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (2016) have demonstrated that visual-spatial abilities in kindergarten are associated with reading performance in first, second and third grade of primary school. M. Kibby et al (2015) emphasise that reading difficulties are related to visual processing problems. Kavale and Fornes (2000) argue that visual memory and visual discrimination are the best predictor of general reading ability.…”
Section: Discussionmentioning
confidence: 99%
“…Stronger visual discrimination abilities were also positively associated with better phonemic awareness skills, presumably because of the association between letter knowledge and phonemic skills, or letter-sound correspondence. Kibby et al (2015) found that visual processing might be intact in reading disabilities when measured with tasks of untimed discrimination and visual short-term memory that do not require sequential processing or allow easy labelling.…”
Section: Phonological Processingmentioning
confidence: 96%
See 1 more Smart Citation
“…Several behavioral studies have focused on SA impairments in children with ADHD (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), although some of the studies did not show the existence of any differences in spatial tasks between the performance quality of children with ADHD and typically developing children (38)(39)(40)(41)(42). The reason for many inconsistencies might be due to the fact that not only the unity of SA is not precisely de ned, but also not even a single appropriate test is used to measure these factors in various researches.…”
Section: Introductionmentioning
confidence: 99%